PEMANFAATAN BAHAN PEWARNA ALAM SEBAGAI ALTERNATIF DALAM PEMBUATAN BATIK TULIS YANG RAMAH LINGKUNGAN - Purwanto _ (IST AKPRIND Yogyakarta, 2018)
The global issue of environmentally friendly raw materials, processes and products is growing. Utilization of the use of natural staining is one alternative way to produce environmentally friendly products, as well as in the use of natural dyes in batik making. Batik is an original intangible heritage of Indonesia and has been recognized internationally through UNESCO's world organization in 2009 and the city of Yogyakarta has been recognized as the